(untitled) (Al-Academy, 2024)
Creativity is an essential feature of graphic design, as designers rely on creativity to create attractive and effective designs that meet the needs of the target audience. In recent years, the field of graphic design has witnessed rapid development in the field of artificial intelligence, as it can help designers create new and diverse creative designs. Graphic design is one of the artistic and technical fields that requires creativity and innovation, but it also faces some challenges and difficulties in the design and implementation process. Therefore, artificial intelligence technology has an important role in improving and facilitating work in this field, by providing many tools and software that use artificial intelligence in design. Graphic design, which is characterized by its ability to provide smart and innovative suggestions and improvements to designers. This research aims to review the importance, benefits and advantages of using artificial intelligence in graphic design, and how it can contribute to enhancing creativity and design efficiency, as well as highlighting the idea that artificial intelligence is an auxiliary factor to intelligence. Humanity, which is irreplaceable. The research concludes by emphasizing the importance and benefits of using artificial intelligence in graphic design, and how it can contribute to enhancing creativity and design efficiency